Pakistan - "Mumtaz, Soofia, (ed.)" (Oxford, 2002)
This collection of papers originated at a Paris seminar. It The volume covers a very broad spectrum of life in Pakistan Pakistan and focuses on political, strategic, cultural, social and gender topics. Hitherto readers have had access to British, American and even Indian studies on Pakistan, while this is the first volume which makes accessible the views of French scholars.
Keywords: Pakistan-Politics